Computed Tomography Enhances Diagnostic Accuracy in Challenging Medial Coronoid Disease Cases: An Imaging Study in Dog Breeding Appeal Cases - Wennemuth, Jan; Tellhelm, Bernd; Eley, Nele; von Pückler, Kerstin (Veterinary and Comparative Orthopaedics and Traumatology, 2020)
Objectives The aim of this study was to determine the radiographic sensitivity in detecting medial coronoid disease (MCD), using computed tomography (CT) as reference in dogs presented for an official second opinion, and to compare the medial coronoid process (MCP) in fragmented and fissured MCP as well as those unaffected by MCD.Materials and Methods The data of dogs, presented for official second opinion radiographs and CT, were reviewed by three board-certified observers and in accordance with the International Elbow Working Group guidelines regarding MCD. Radiographic delineation, radiopacity and Hounsfield Units (HU) of the MCP were recorded additionally and the correlation between radiography and CT was investigated.Results Sensitivity and specificity of radiography compared with CT yielded values of 83.6% for the former and 83.5% for the latter. False-negative grading in radiography correlated significantly (p = 0.0001) with a present fissure line in CT. The mean delineation (p = 0.03) and mean HU of fragmented MCP (p = 0.0045) were significantly reduced compared with fissured MCP and no significant differences in measured HU for fissured MCP were detected in comparison to elbows unaffected by MCD.Conclusion The results of the present study show substantial agreement between radiography and CT in second opinion cases. However, sensitivity is reduced compared with not preselected cases. A present fissure line in CT was significantly associated with a false-negative grading in radiography. Therefore, CT imaging of the elbows is strongly recommended in cases of appeal.
Keywords: canine; elbow dysplasia; medial coronoid disease; CT; fissures